Improved Algorithm of LTE Random Access Preamble Detection under the High Speed Condition - Liu Jinhu; Ma Jian Ting (Institute of Advanced Engineering and Science, 2013)
This paper improves the algorithm of preamble detection in LTE system random access under the condition of high speed. Improved algorithm mainly adopts peak filter to estimate noise and to set dynamic threshold, concerning that the constrained cyclic shift ZC array used in high speed subdistrict accumulate the useful correlated energy in incoherent way in order to avoid missing condition caused by frequency offset to increase detection rate. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3091